ANALYSIS OF COMMISSION PAYMENT TO ONLINE TRAVEL AGENT IN IMPROVING ROOM REVENUE AT AYODYA RESORT BALI - Ni Made Thrisna Puspita Dewi; I Gusti Putu Sutarma; I Ketut Suarta (Politeknik Negeri Bali, 2018)
The role of Online Travel Agent is very important in contributing to the room revenue, which is as the source of business to business. Room sales are made through online travel agent is higher than other reservation sources. The purpose of this research is intended to know the effectivity of online travel agent in order to increase rooms revenue at Ayodya Resort Bali. The data we collected by interviews, participatory observation, and documentations. Type of data were used in this research are qualitative and quantitative. In this research, there were 2 person selected as a respondent using purposive sampling method to determine the informant. The technique of analysis used in this research is descriptive qualitative whis is helped by program Microsot Excel 2013. The data validity is uses triangulation of source. Based on the calculation, in terms of giving commission to online travel agents still need to be re-evaluated caused besides Booking.com, Agoda.com, and Expedia, there are 9 (nine) online travel agents such as Orbitz, Travel Hotel, Asiaroom.com, Rakuten, Asia Travel, Traveloka, Tiket.com, Hoterip, and Pegi-pegi that have not been effective yet in improving room revenue it can be seen from the GAP of revenue received that is still far away from the revenue received by Booking, com, Agoda.com and Expedia. However, in the era of globalization, the prospect of online travel agent is still very potential to be applied and developed in an effort to get maximum room revenue provit in Ayodya Resort Bali